How perceptions of labor market opportunities predict happiness: evidence from natural field experiments - Fernandez-Urbano, Roger (Frontiers in Sociology, 2025)
IntroductionSubjective variables related to the labor market have long been recognized to be strongly associated with individuals' happiness. However, most existing research relied on correlational analyses, which have been insufficient in establishing causation. Establishing causal links is crucial for disentangling reverse causality as well as addressing order-of-effect and omitted variable biases, thereby determining whether and how subjective labor market perceptions directly impact happiness. Moreover, prior studies have primarily focused on personal labor market concerns, largely overlooking perceptions of labor market opportunities at the macro level. Recognizing these broader perceptions is vital for understanding behavioral outcomes at both individual and societal levels, and for understanding persistent levels of structural unemployment and particular policy preferences.MethodsThis study addresses these gaps by conducting harmonized natural field experiments in Pennsylvania, U.S., and Barcelona, Spain, to examine how perceptions of macro-level labor market opportunities impact happiness.Results and discussionThe results reveal that in Barcelona only positive perceptions have an effect and increase happiness, whereas in Pennsylvania only negative perceptions impact happiness and do so detrimentally. This discrepancy is attributed to subtle, experimentally induced shifts in the framing of truthful macroeconomic information. The discussion proposes a cultural bias mechanism to account for these differences. Heterogeneous effects of the treatments in terms of social background and subjective health are also discussed. The findings hold significant implications for policymaking and organizational strategies, underscoring the importance of understanding how perceived macro-labor market opportunities shape happiness.